Thermoplastic resin composition and molded article

The thermoplastic resin composition with ethylene/α-olefin/nonconjugated diene copolymer, mineral oil, and phthalate ester addresses die swell issues, enhancing dimensional accuracy and reducing waste in extrusion molding.

JP7604709B1Active Publication Date: 2024-12-23SUMITOMO CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024105343
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2024-12-23
Estimated Expiration
2044-06-28

Smart Images

  • Figure 0007604709000001
    Figure 0007604709000001
  • Figure 0007604709000002
    Figure 0007604709000002
  • Figure 0007604709000003
    Figure 0007604709000003
Patent Text Reader

Abstract

The present invention aims to provide a thermoplastic resin composition and a molded article having a relatively small die swelling ratio during extrusion molding. [Solution] The thermoplastic resin composition of the present invention contains (A) an ethylene-α-olefin-non-conjugated diene copolymer, (B) a mineral oil, and (C) a phthalate ester, and the content of the (C) phthalate ester is 5 ppm or more and 10,000 ppm or less per 100 parts by mass of the (A) ethylene-α-olefin-non-conjugated diene copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition and a molded article. [Background technology]

[0002] Conventionally, thermoplastic resin compositions are highly recyclable, suitable for injection molding, and have excellent product performance such as strength and flexibility, and therefore have been widely used as materials for automobile parts, etc. As such a thermoplastic resin composition, for example, Patent Document 1 discloses a resin composition for automobile door grommets that contains an olefin copolymer rubber, an olefin resin, and a hydrocarbon rubber softener. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-265715 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional thermoplastic resin compositions have a problem that, for example, immediately after being extruded from a die during extrusion molding, the cross-sectional dimensions of the composition expand more than the exit dimensions of the die. Therefore, there is a demand for reducing the expansion rate (die swell ratio) during extrusion molding and improving the dimensional accuracy of the resulting molded products. It is expected that by improving the dimensional accuracy of not only extrusion molded products but also blow molded products, injection molded products, etc., the yield can be improved, thereby reducing material loss and reducing the required energy.

[0005] The present invention has been made in view of the above problems, and an object of the present invention is to provide a thermoplastic resin composition and a molded article which have a relatively small die swelling ratio during extrusion molding. [Means for solving the problem]

[0006] The thermoplastic resin composition according to the present invention comprises (A) an ethylene-α-olefin-non-conjugated diene copolymer, (B) a mineral oil, and (C) a phthalate ester; (C) The content of phthalate ester is 5 ppm or more and 10,000 ppm or less based on 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A).

[0007] The molded article according to the present invention contains a thermoplastic resin composition. Effect of the Invention

[0008] According to the present invention, it is possible to provide a thermoplastic resin composition and a molded article having a relatively small die swelling ratio during extrusion molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0010] [Thermoplastic resin composition] The thermoplastic resin composition according to this embodiment contains (A) an ethylene-α-olefin-non-conjugated diene copolymer (hereinafter, sometimes simply referred to as (A)), (B) a mineral oil (hereinafter, sometimes simply referred to as (B)), and (C) a phthalate ester (hereinafter, sometimes simply referred to as (C)).

[0011] <(A) Ethylene-α-olefin-non-conjugated diene copolymer> (A) Ethylene-α-olefin-non-conjugated diene copolymer is a copolymer containing monomer units derived from ethylene, monomer units derived from α-olefin, and monomer units derived from non-conjugated diene. (A) may be used alone or in combination of two or more kinds.

[0012] The α-olefin is preferably an α-olefin having 3 to 20 carbon atoms. Examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. Among these, the α-olefin having 3 to 20 carbon atoms is preferably propylene or 1-butene, and more preferably propylene. The α-olefin may be used alone or in combination of two or more kinds.

[0013] Examples of the non-conjugated dienes include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-no Examples of the non-conjugated diene include cyclic non-conjugated dienes such as norbornene, 5-isopropylidene-2-norbornene, and 6-chloromethyl-5-isopropenyl-2-norbornene; and trienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene, and 4-ethylidene-8-methyl-1,7-nanodiene. Among these, the non-conjugated diene is preferably 5-ethylidene-2-norbornene or dicyclopentadiene. The non-conjugated diene may be used alone or in combination of two or more kinds.

[0014] With the total amount of the (A) ethylene-α-olefin-non-conjugated diene copolymer taken as 100 mass%, the content of monomer units derived from ethylene is usually 30 mass% or more and 80 mass% or less, and preferably 40 mass% or more and 80 mass% or less, the content of monomer units derived from α-olefin is usually 5 mass% or more and 50 mass% or less, and preferably 15 mass% or more and 45 mass% or less, and the content of monomer units derived from non-conjugated diene is preferably 4 mass% or more and 15 mass% or less, and more preferably 6 mass% or less and 15 mass% or less.

[0015] The (A) ethylene-α-olefin-non-conjugated diene copolymer is preferably an ethylene-propylene-5-ethylidene-2-norbornene copolymer, an ethylene-propylene-dicyclopentadiene copolymer, an ethylene-propylene-1,4-hexadiene copolymer, or an ethylene-propylene-5-vinyl-2-norbornene copolymer.

[0016] In one embodiment, the (A) ethylene-α-olefin-non-conjugated diene copolymer is an ethylene-propylene-5-ethylidene-2-norbornene copolymer having a content of monomer units derived from ethylene of 40% by mass or more and 80% by mass or less, a content of monomer units derived from propylene of 15% by mass or more and 45% by mass or less, and a content of monomer units derived from 5-ethylidene-2-norbornene of 3% by mass or more and 15% by mass or less.

[0017] The contents of the monomer units derived from ethylene, the monomer units derived from α-olefins, and the monomer units derived from non-conjugated dienes can be determined by infrared spectroscopy (IR method). Specifically, the (A) ethylene-α-olefin-non-conjugated diene copolymer is formed into a film having a thickness of about 0.5 mm, and then, using an infrared spectrophotometer, the peaks derived from non-conjugated dienes of the film (1688 cm in the case of a peak derived from 5-ethylidene-2-norbornene) are measured. -1The content of the monomer units derived from the non-conjugated diene in the copolymer is calculated by measuring the absorption peak of the non-conjugated diene in the copolymer. Next, the copolymer is formed into a film having a thickness of about 0.1 mm, and the infrared absorption spectrum of the film is measured using an infrared spectrophotometer. The ratio of the monomer units derived from ethylene and the monomer units derived from the α-olefin is calculated according to the method described in the literature (Characterization of Polyethylene by Infrared Absorption Spectroscopy, Takayama, Usami, et al., or Die Makromolekulare Chemie, 177, 461 (1976) by McRae, MA, Madam S, WF, et al.), and the content of the monomer units derived from ethylene and the content of the monomer units derived from the α-olefin can be calculated from the ratio and the content of the monomer units derived from the non-conjugated diene.

[0018] (A) Ethylene-α-olefin-non-conjugated diene copolymer can be obtained by polymerization using a known method, such as a method of polymerization using a polymerization catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst in an inert solvent such as hexane, heptane, toluene, or xylene.

[0019] (A) Mooney viscosity (ML 1+4 100°C) is preferably 40 or more, more preferably 50 or more. 1+4 100°C) is preferably 300 or less, more preferably 250 or less, and further preferably 200 or less. 1+4 100°C) in the above range, a molded product having excellent mechanical strength and excellent appearance can be obtained. 1+4 100℃) is measured according to JIS K6300 and is 1+4 "100°C" has the following meaning: M: Mooney viscosity L: Uses a large rotor 100℃: Measurement temperature 1+4: The measured value when the sample was heated for 1 minute and then rotated at 2 rpm for 4 minutes.

[0020] The JIS K 6253 A hardness of the (A) ethylene-α-olefin-non-conjugated diene copolymer is preferably 85 or less.

[0021] The (A) ethylene-α-olefin-non-conjugated diene copolymer may be uncrosslinked or may be partially crosslinked as long as it exhibits thermoplasticity. The (A) ethylene-α-olefin-non-conjugated diene copolymer may be crosslinked by various crosslinking agents such as sulfur, peroxides, sulfur-containing organic compounds, alkylphenols, and formaldehyde resins.

[0022] <(B) Mineral oil> (B) Mineral oil is a high boiling point fraction of petroleum, and preferably has an average molecular weight of 300 or more and 1500 or less, and a pour point of 0° C. or less. (B) Mineral oil includes, for example, paraffinic mineral oil, naphthenic mineral oil, aromatic mineral oil, etc. (B) Mineral oil is preferably paraffinic mineral oil or naphthenic mineral oil, and more preferably paraffinic mineral oil.

[0023] The (B) mineral oil may be mixed with the (A) ethylene-α-olefin-non-conjugated diene copolymer, i.e., the (A) ethylene-α-olefin-non-conjugated diene copolymer may be extended with the (B) mineral oil.

[0024] When the mineral oil (B) is added as an extender oil to the ethylene-α-olefin-non-conjugated diene copolymer (A), a known method can be used for the addition, and examples of the method include a method in which the two are mechanically kneaded using a kneading device such as a roll or a Banbury mixer, a method in which (B) is added to a solution of (A) produced in a solution state, and then the solvent is removed by a method such as steam stripping, and the like.

[0025] When (B) mineral oil is added as an extender oil to (A) ethylene-α-olefin-non-conjugated diene copolymer, the Mooney viscosity (ML 1+4 100°C) is preferably 5 or more and 300 or less, more preferably 10 or more and 250 or less, and further preferably 40 or more and 200 or less. 1+4 100°C) can be measured in the same manner as in (A) above.

[0026] The content of the (B) mineral oil is preferably 30 parts by mass or more and 200 parts by mass or less, and more preferably 50 parts by mass or more and 150 parts by mass or less, per 100 parts by mass of the (A) ethylene-α-olefin-non-conjugated diene copolymer.

[0027] <(C) Phthalate esters> Examples of (C) phthalate esters include diisononyl phthalate, di-2-ethylhexyl phthalate, dibutyl phthalate, butyl benzyl phthalate, diisodecyl phthalate, di-normal octyl phthalate, and isomers thereof. (C) phthalate esters are preferably at least one selected from the group consisting of diisononyl phthalate, di-2-ethylhexyl phthalate, and isomers thereof, and more preferably diisononyl phthalate and its isomers. The isomers of diisononyl phthalate include multiple isomers such as dimethylheptanol and methyloctanol in the alcohol portion. (C) may be used alone or in combination of two or more.

[0028] The content of (C) phthalate ester is 5 ppm or more and 10,000 ppm or less, and preferably 50 ppm or more and 5,000 ppm or less, based on 100 parts by mass of (A) ethylene-α-olefin-non-conjugated diene copolymer, from the viewpoint of reducing the die swelling ratio during extrusion molding.

[0029] <(D) Olefin-based polymer> The thermoplastic resin composition according to the present embodiment may further contain (D) an olefin-based polymer (excluding (A) the ethylene-α-olefin-non-conjugated diene copolymer) (hereinafter, sometimes simply referred to as (D)). The (D) olefin-based polymer is preferably at least one selected from the group consisting of ethylene-based polymers and propylene-based polymers.

[0030] The ethylene-based polymer is a polymer containing more than 50% by mass of monomer units derived from ethylene. Examples of the ethylene-based polymer include ethylene homopolymers and ethylene-α-olefin copolymers. The ethylene-based polymer is preferably an ethylene-α-olefin copolymer. The ethylene-based polymer may be used alone or in combination of two or more kinds.

[0031] The ethylene homopolymer is preferably an ethylene homopolymer obtained by polymerizing ethylene by a high-pressure method, and is produced, for example, by polymerizing ethylene in the presence of a radical generator using a tank reactor or a tubular reactor at a polymerization pressure of 140 MPa or more and 300 MPa or less and a polymerization temperature of 200° C. or more and 300° C. or less.

[0032] The density of the ethylene homopolymer is preferably 910 kg / m from the viewpoint of improving heat resistance. 3 More preferably, it is 915 kg / m 3 More preferably, it is 920 kg / m 3 The density is measured according to the method A specified in JIS K7112-1980 after annealing as specified in JIS K6760-1995.

[0033] The ethylene-α-olefin copolymer is a copolymer containing a monomer unit derived from ethylene and a monomer unit derived from an α-olefin. The α-olefin is preferably an α-olefin having 3 to 10 carbon atoms. Examples of the α-olefin having 3 to 10 carbon atoms include propylene, 1-butene, 2-methylpropene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. Among these, the α-olefin having 3 to 10 carbon atoms is preferably propylene, 1-butene, or 1-octene. The α-olefin may be used alone or in combination of two or more kinds.

[0034] With the total amount of the ethylene-α-olefin copolymer taken as 100% by mass, the content of monomer units derived from ethylene is preferably more than 50% by mass and not more than 90% by mass, more preferably from 55% by mass to 85% by mass, and even more preferably from 60% by mass to 75% by mass, and the content of monomer units derived from α-olefin is preferably from 10% by mass to less than 50% by mass, more preferably from 15% by mass to 45% by mass, and even more preferably from 25% by mass to 40% by mass.

[0035] The content of the monomer unit derived from ethylene and the monomer unit derived from α-olefin can be determined by infrared spectroscopy (IR method). Specifically, an infrared absorption spectrum of an ethylene-α-olefin copolymer is measured using an infrared spectrophotometer, and the content of the monomer unit derived from ethylene and the monomer unit derived from α-olefin is calculated according to the method described in the literature (Characterization of Polyethylene by Infrared Absorption Spectroscopy, Takayama, Usami, et al., or Die Makromolekulare Chemie, 177, 461 (1976) by McRae, MA, Madam S, WF, et al.).

[0036] The ethylene-α-olefin copolymer may contain other monomer units other than ethylene and α-olefins having 3 to 10 carbon atoms. Examples of the other monomers include conjugated dienes having 4 to 8 carbon atoms such as 1,3-butadiene, 2-methyl-1,3-butadiene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene; vinyl carboxylates such as vinyl acetate; unsaturated carboxylates such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, and ethyl methacrylate; and unsaturated carboxylic acids such as acrylic acid and methacrylic acid. The other monomers may be used alone or in combination of two or more.

[0037] The content of monomer units derived from other monomers is preferably 30% by mass or less, more preferably 20% by mass or less, based on the total amount of the ethylene-α-olefin copolymer being 100% by mass. The content of monomer units derived from other monomers can be determined by infrared spectroscopy (IR method). Specifically, an infrared spectrophotometer is used to measure the peak intensity of the peak derived from the other monomers in the ethylene-α-olefin copolymer, and the content of monomer units derived from the other monomers is calculated from the peak intensity.

[0038] Examples of the ethylene-α-olefin copolymer include an ethylene-propylene copolymer, an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer, an ethylene-1-octene copolymer, an ethylene-propylene-1-butene copolymer, an ethylene-propylene-1-hexene copolymer, an ethylene-propylene-1-octene copolymer, etc. The ethylene-α-olefin copolymer is preferably an ethylene-propylene copolymer.

[0039] Examples of methods for producing ethylene-α-olefin copolymers include copolymerization of ethylene and α-olefin in the presence of a known complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, a nonmetallocene complex, etc. Examples of polymerization methods include slurry polymerization, solution polymerization, bulk polymerization, and gas phase polymerization.

[0040] The propylene-based polymer is a polymer containing more than 50% by mass of monomer units derived from propylene. The propylene-based polymer is suitable for forming the sea phase of the sea-island structure of the thermoplastic resin composition. Examples of the propylene-based polymer include a propylene homopolymer, a heterophasic polymer material, and a propylene random copolymer. The propylene-based polymer is preferably at least one selected from the group consisting of a propylene homopolymer, a heterophasic polymer material, and a propylene random copolymer, and more preferably a propylene homopolymer, a heterophasic polymer material, or a propylene random copolymer. The propylene-based polymer may be used alone or in combination of two or more kinds.

[0041] Examples of propylene random copolymers include: (1) A propylene-ethylene random copolymer, in which the content of monomer units derived from propylene is 90% by mass or more and 99.5% by mass or less, and the content of monomer units derived from ethylene is 0.5% by mass or more and 10% by mass or less, relative to 100% by mass of the total amount of monomer units derived from propylene and monomer units derived from ethylene; (2) A propylene-ethylene-α-olefin random copolymer in which the content of monomer units derived from propylene is 81% by mass or more and 99% by mass or less, the content of monomer units derived from ethylene is 0.5% by mass or more and 9.5% by mass or less, and the content of monomer units derived from α-olefins having 4 to 10 carbon atoms is 0.5% by mass or more and 9.5% by mass or less, relative to 100% by mass of the total amount of monomer units derived from propylene, monomer units derived from ethylene, and monomer units derived from α-olefins having 4 to 10 carbon atoms; or (3) A propylene-α-olefin random copolymer in which the content of monomer units derived from propylene is 90% by mass or more and 99.5% by mass or less, and the content of monomer units derived from α-olefins having 4 to 10 carbon atoms is 0.5% by mass or more and 10% by mass or less, relative to 100% by mass of the total amount of monomer units derived from propylene and monomer units derived from α-olefins having 4 to 10 carbon atoms.

[0042] Examples of the α-olefin having 4 to 10 carbon atoms in the above (2) and (3) include linear α-olefins such as 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, etc.; and branched α-olefins such as 3-methyl-1-butene, 3-methyl-1-pentene, etc. The α-olefins having 4 to 10 carbon atoms may be used alone or in combination of two or more kinds.

[0043] Methods for producing propylene homopolymers and propylene random copolymers include, for example, slurry polymerization, solution polymerization, bulk polymerization, and gas phase polymerization using known complex catalysts such as Ziegler-Natta catalysts, metallocene complexes, and nonmetallocene complexes.

[0044] The heterophasic polymerization material is a polymerization material comprising a propylene homopolymer component (I) and an ethylene copolymer component (II) having monomer units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms and monomer units derived from ethylene. The heterophasic polymerization material preferably contains 70% by mass or more and 90% by mass or less of propylene homopolymer component (I) and 10% by mass or more and 30% by mass or less of ethylene copolymer component (II), more preferably 75% by mass or more and 90% by mass or less and 10% by mass or more and 25% by mass or less of ethylene copolymer component (II), relative to 100% by mass of the total amount of the heterophasic polymerization material.

[0045] The α-olefin having 4 or more carbon atoms in the ethylene copolymer component (II) is preferably an α-olefin having 4 to 20 carbon atoms. Examples of the α-olefin having 4 to 20 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene. The α-olefin having 4 or more carbon atoms is more preferably an α-olefin having 4 to 10 carbon atoms, and further preferably 1-butene, 1-hexene, or 1-octene. The α-olefin having 4 or more carbon atoms may be used alone or in combination of two or more kinds.

[0046] The content of the monomer unit derived from ethylene in the ethylene copolymer component (II) is preferably 22% by mass or more and 90% by mass or less, more preferably 25% by mass or more and 80% by mass or less, and even more preferably 27% by mass or more and 70% by mass or less, based on 100% by mass of the total amount of the monomer unit derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms, and the monomer unit derived from ethylene. The content of the monomer unit derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the ethylene copolymer component (II) is preferably 20% by mass or more and 78% by mass or less, more preferably 30% by mass or more and 75% by mass or less, and even more preferably 40% by mass or more and 73% by mass or less, based on 100% by mass of the total amount of the monomer unit derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms, and the monomer unit derived from ethylene. The content of monomer units derived from ethylene and the content of monomer units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the ethylene copolymer component (II) can be determined, for example, by infrared spectroscopy (IR method). Specifically, the infrared absorption spectrum of the ethylene copolymer component (II) is measured using an infrared spectrophotometer, and the content of units derived from ethylene and the content of monomer units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms are calculated according to the method described in the literature (Characterization of Polyethylene by Infrared Absorption Spectroscopy, Takayama, Usami, et al., or Die Makromolekulare Chemie, 177, 461 (1976) by Mc Rae, MA, Madam S, WF, et al.).

[0047] Examples of the ethylene copolymer component (II) include propylene-ethylene copolymer, ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, propylene-ethylene-1-butene copolymer, propylene-ethylene-1-hexene copolymer, propylene-ethylene-1-octene copolymer, etc. The ethylene copolymer component (II) is preferably a propylene-ethylene copolymer or a propylene-ethylene-1-butene copolymer.

[0048] Examples of methods for producing heterophasic polymerized materials include a method of multi-stage polymerization using a polymerization catalyst.

[0049] Examples of polymerization catalysts used in the production of heterophasic polymerization materials include Ziegler catalysts, Ziegler-Natta catalysts, catalysts consisting of a transition metal compound of Group 4 of the periodic table having a cyclopentadienyl ring and an alkylaluminoxane, transition metal compounds of Group 4 of the periodic table having a cyclopentadienyl ring, compounds that react with the transition metal compounds to form ionic complexes, and catalysts consisting of organoaluminum compounds.

[0050] In addition, a prepolymerization catalyst may be used in the presence of the above-mentioned polymerization catalyst. Examples of the prepolymerization catalyst include those described in JP-A-61-218606, JP-A-61-287904, JP-A-5-194685, JP-A-7-216017, JP-A-9-316147, JP-A-10-212319, and JP-A-2004-182981.

[0051] Examples of polymerization methods for producing heterophasic polymeric materials include bulk polymerization, solution polymerization, slurry polymerization, and gas phase polymerization. Examples of inert hydrocarbon solvents used in solution polymerization and slurry polymerization include propane, butane, isobutane, pentane, hexane, heptane, and octane. Two or more of these polymerization methods may be combined, and may be either batch or continuous. The polymerization method for producing heterophasic polymeric materials is preferably continuous gas phase polymerization, or bulk-gas phase polymerization, in which bulk polymerization and gas phase polymerization are carried out continuously.

[0052] The melt flow rate (MFR) of the propylene polymer measured at a temperature of 230° C. and a load of 2.16 kg according to JIS K7210 is preferably 60 g / 10 min or less, more preferably 30 g / 10 min or less, and even more preferably 10 g / 10 min or less, from the viewpoint of reducing the compression set of the thermoplastic resin composition. The MFR of the propylene polymer is preferably 0.05 g / 10 min or more, more preferably 0.1 g / 10 min or more. The MFR of the propylene polymer is preferably 0.05 g / 10 min or more and 60 g / 10 min or less, more preferably 0.1 g / 10 min or more and 30 g / 10 min or less, and even more preferably 0.1 g / 10 min or more and 10 g / 10 min or less. When two or more propylene polymers are used in combination, the MFR of the propylene polymer with the largest content is taken as the MFR of the propylene polymer.

[0053] The content of the olefin polymer (D) is preferably 10 parts by mass or more and 200 parts by mass or less, and more preferably 20 parts by mass or more and 80 parts by mass or less, per 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A).

[0054] The thermoplastic resin composition of the present embodiment may further contain other additives.

[0055] Examples of other additives include crosslinking agents, crosslinking assistants, inorganic fillers, organic fillers, ultraviolet absorbers, heat stabilizers, light stabilizers, antistatic agents, nucleating agents, pigments, adsorbents, metal chlorides, silicone compounds, antibacterial agents, antiviral agents, antimoss agents, and antialgae agents.

[0056] Examples of the inorganic filler include talc, calcium carbonate, and calcined kaolin.

[0057] Examples of the organic filler include fiber, wood powder, and cellulose powder.

[0058] Examples of the ultraviolet absorbing agent include a benzotriazole-based ultraviolet absorbing agent, a tridiamine-based ultraviolet absorbing agent, an anilide-based ultraviolet absorbing agent, and a benzophenone-based ultraviolet absorbing agent.

[0059] Examples of the light stabilizer include hindered amine light stabilizers and benzoate light stabilizers.

[0060] Examples of the pigment include inorganic pigments and organic pigments. Examples of the inorganic pigment include carbon black, titanium oxide, calcium carbonate, zinc oxide, lead carbonate, barium sulfate, cerium oxide, kaolin clay, zinc oxide, red iron oxide, molybdenum orange, cobalt blue, ultramarine blue, manganese violet, etc. Examples of the organic pigment include madder lake, pink madder, dragon's blood, cochineal, sepia, permanent red, fast yellow, naphthol red, phthalocyanine blue, etc.

[0061] Examples of metal chlorides include iron chloride and calcium chloride.

[0062] In one embodiment, the thermoplastic resin composition according to the present embodiment further contains at least one selected from the group consisting of calcium carbonate and carbon black.

[0063] The content of the other additives is preferably 40% by mass or less, relative to 100% by mass of the total mass of the thermoplastic resin composition.

[0064] Each component contained in the thermoplastic resin composition according to this embodiment may contain carbon-14 (14C) as a constituent element, may be material recycled, or may be chemically recycled.

[0065] The concentration of carbon-14 (14C) contained in each component of the thermoplastic resin composition is determined as pMC (percentage of moderate carbon: unit %) by the AMS (Accelerator mass spectrometry) method specified in ISO 16620-2:2019.

[0066] Carbon-14 (14C) is contained in a certain proportion in carbon dioxide in the atmosphere, and it is known that plants that grow by absorbing carbon dioxide from the atmosphere, such as corn and trees, contain 14C. It is also known that fossil resources such as petroleum, which are thought to have been stored underground for a long time, contain almost no carbon-14 (14C). Therefore, by using plant-derived substances as raw materials for the monomers used to manufacture each component contained in the thermoplastic resin composition, it is possible to contain carbon-14 (14C) in the constituent elements of the ethylene-α-olefin-non-conjugated diene copolymer.

[0067] Fossil resource-derived monomers are derived from underground carbon resources such as petroleum, coal, and natural gas, and generally contain almost no carbon-14 (14C). Methods for producing fossil resource-derived monomers include known methods, such as cracking petroleum-derived naphtha and ethane, and dehydrogenating ethane and propane to produce olefins.

[0068] Plant-derived monomers are derived from carbon circulating on the earth's surface as plants and animals, and generally contain a certain percentage of carbon-14 (14C). Methods for producing plant-derived monomers include known methods, such as cracking bionaphtha, vegetable oil, animal oil, etc., dehydrogenation of biopropane, methods of separating alcohol from fermented products such as sugar extracted from plant raw materials such as sugarcane and corn, and subjecting it to a dehydration reaction (JP Patent Publication No. 2010-511634, JP Patent Publication No. 2011-506628, JP Patent Publication No. 2013-503647, etc.), and methods of subjecting ethylene obtained from plant-derived ethanol to a metathesis reaction with n-butene (WO2007 / 055361, etc.).

[0069] Chemical recycling monomers are derived from carbon generated by decomposition and combustion of waste, and the carbon 14 (14C) content varies depending on the waste. Methods for producing chemical recycling monomers include known methods, such as a method of thermally decomposing waste plastics (JP Patent Publication No. 2017-512246, etc.), a method of cracking waste vegetable oil, waste animal oil, etc. (JP Patent Publication No. 2018-522087, etc.), and a method of gasifying, converting to alcohol, and dehydrating waste such as food waste, biomass waste, food waste, waste oil, waste wood, waste paper, and waste plastics (JP Patent Publication No. 2019-167424, WO2021 / 006245, etc.).

[0070] The thermoplastic resin composition according to the present embodiment is extruded at a temperature of 220° C. and a shear rate of 1216 sec. -1 is preferably 50 Pa·sec or more and 600 Pa·sec or less, more preferably 70 Pa·sec or more and 400 Pa·sec or less, and even more preferably 100 Pa·sec or more and 350 Pa·sec or less.

[0071] The thermoplastic resin composition according to this embodiment can be obtained by melt-kneading each component.

[0072] Examples of the melt-kneading device include an open-type mixing roll, a non-open-type Banbury mixer, an extruder, a kneader, and a continuous mixer. The melt-kneading device is preferably a non-open-type device. All the components to be kneaded may be melt-kneaded at once, or a part of the components may be kneaded and then the remaining components may be added and melt-kneaded, or the melt-kneading may be performed once or twice or more. The temperature during melt-kneading is preferably 150°C or higher and 250°C or lower, and the time is preferably 30 seconds or higher and 30 minutes or lower. The components to be kneaded may be added in any order or simultaneously.

[0073] [Molded body] The molded article according to this embodiment contains the above-mentioned thermoplastic resin composition.

[0074] The molded article can be molded by a known molding method such as extrusion molding using a conventional apparatus used for molding thermoplastic resin compositions.

[0075] The molded article according to this embodiment can be used, for example, for bathroom and bathtub parts, rubber-related parts, automobile parts, electrical parts, home appliance parts, furniture components, building components, footwear parts, sports equipment parts, medical and nursing care-related products, and other industrial materials.

[0076] The thermoplastic resin composition and molded article according to this embodiment are not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. In addition, the configurations of the embodiments other than the above may be arbitrarily adopted and combined, and the configurations of one of the above embodiments may be applied to the configurations of the other embodiments.

[0077] The present invention includes the following aspects. [1] A composition comprising: (A) an ethylene-α-olefin-non-conjugated diene copolymer; (B) a mineral oil; and (C) a phthalate ester; (C) A thermoplastic resin composition having a phthalate ester content of 5 ppm or more and 10,000 ppm or less based on 100 parts by mass of (A) the ethylene-α-olefin-non-conjugated diene copolymer. [2] The thermoplastic resin composition according to [1], wherein the content of the mineral oil (B) is 30 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A). [3] The thermoplastic resin composition according to [1] or [2], further comprising at least one selected from the group consisting of calcium carbonate and carbon black. [4] The thermoplastic resin composition according to any one of [1] to [3], further comprising (D) an olefin-based polymer (excluding (A) an ethylene-α-olefin-non-conjugated diene copolymer). [5] The thermoplastic resin composition according to [4], wherein the olefin-based polymer (D) is at least one selected from the group consisting of ethylene-based polymers and propylene-based polymers. [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the content of (C) phthalate ester is 50 ppm or more and 5,000 ppm or less per 100 parts by mass of (A) the ethylene-α-olefin-non-conjugated diene copolymer. [7] The thermoplastic resin composition according to any one of [1] to [6], wherein the content of the mineral oil (B) is 50 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A). [8] The thermoplastic resin composition according to any one of [1] to [7], wherein the phthalate ester (C) is diisononyl phthalate. [9] (A) The thermoplastic resin composition according to any one of [1] to [8], wherein the content of monomer units derived from a non-conjugated diene in the ethylene-α-olefin-non-conjugated diene copolymer is 4 mass% or more and 15 mass% or less.

[10] (A) Mooney viscosity (ML 1+4 100°C) is 40 or more.

[11] Temperature: 220°C, shear rate: 1216 sec -1The thermoplastic resin composition according to any one of [1] to

[10] , having a shear viscosity of 50 Pa·sec or more and 600 Pa·sec or less.

[12] A molded article comprising the thermoplastic resin composition according to any one of [1] to

[11] . EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The measured values ​​of each item in the examples and comparative examples were measured by the following methods.

[0079] (Physical property measurement method) [Mooney Viscosity (ML 1+4 100℃)] The measurement was carried out in accordance with JIS K6300. When components (A) and (B) were mixed in advance, the Mooney viscosity (ML 1+4 100℃) was calculated using the following formula (1). log(ML1 / ML2)=0.0066(△PHR) (1) ML1: Mooney viscosity of component (A) ML2: Mooney viscosity of a mixture of component (A) and component (B) △PHR: Content of component (B) per 100 parts by mass of component (A)

[0080] [Content of monomer units derived from ethylene and monomer units derived from 5-ethylidene-2-norbornene (unit: mass%)] The measurement was carried out by infrared spectroscopy (IR method). Specifically, the measurement was carried out by the following method. An ethylene-propylene-5-ethylidene-2-norbornene copolymer was formed into a film having a thickness of about 0.5 mm. Using an infrared spectrophotometer, the peak (1688 cm) derived from 5-ethylidene-2-norbornene of the obtained film was measured. -1The intensity of the absorption peak of the ethylene-propylene-5-ethylidene-2-norbornene copolymer was measured to calculate the content of the monomer derived from 5-ethylidene-2-norbornene in the copolymer. Next, the ethylene-propylene-5-ethylidene-2-norbornene copolymer was newly molded into a film having a thickness of about 0.1 mm. The infrared absorption spectrum of the obtained film was measured using an infrared spectrophotometer, and the content of the monomer unit derived from ethylene was calculated according to the method described in the literature (Characterization of Polyethylene by Infrared Absorption Spectroscopy, Takayama, Usami, et al., or Die Makromolekulare Chemie, 177, 461 (1976) Mc Rae, MA, Madam S, WF, et al.).

[0081] [Measurement of average shear viscosity and average die swell ratio] The average shear viscosity and average die swell ratio were measured using a capillary die with a capillary length of 40 mm and a capillary diameter of 1.0 mm, using a CAPILOGRAPH F1 manufactured by Toyo Seiki Seisakusho Co., Ltd. The test temperature was 220°C, the preheating time was 5 minutes, the residence time was 5 minutes, and the viscosity was 364.8 sec -1 , 1216sec -1 Measurements were performed at two shear rates: 1216 sec -1 Shear viscosity at 364.8sec -1 , 1216sec -1 The average values ​​of the die swell ratio at the two shear rates were calculated. The measurements of the shear viscosity and the die swell ratio were carried out twice, and the average values ​​of the two measurement results were taken as the average shear viscosity and the average die swell ratio.

[0082] (Thermoplastic resin composition) (A1+B1): SK Corporation EPDM product name "S6800WF" (a mixture of 100 parts by mass of A1 (ethylene-propylene-5-ethylidene-2-norbornene copolymer) and 100 parts by mass of paraffinic mineral oil), Mooney viscosity (ML 1+4 100°C) = 57, the content of monomer units derived from ethylene in (A1) = 69 mass%, the content of monomer units derived from 5-ethylidene-2-norbornene in (A1) = 9 mass% (A2+B2): EPDM manufactured by Sumitomo Chemical Co., Ltd., product name "Esprene 670F" (a mixture of 100 parts by mass of A2 (ethylene-propylene-5-ethylidene-2-norbornene copolymer) and 100 parts by mass of paraffinic mineral oil), Mooney viscosity (ML 1+4 100°C) = 61, the content of monomer units derived from ethylene in (A2) = 66 mass%, the content of monomer units derived from 5-ethylidene-2-norbornene in (A2) = 4 mass% (A3+B3): SK Corporation EPDM product name "S6090WF" (a mixture of 100 parts by mass of A3 (ethylene-propylene-5-ethylidene-2-norbornene copolymer) and 50 parts by mass of paraffinic mineral oil), Mooney viscosity (ML 1+4 100°C) = 75, the content of monomer units derived from ethylene in (A3) = 66 mass%, the content of monomer units derived from 5-ethylidene-2-norbornene in (A3) = 6 mass% (A4): Dow EPDM product name "Keltan Eco5470" (A4 (ethylene-propylene-5-ethylidene-2-norbornene copolymer 100 parts by mass), Mooney viscosity (ML 1+4 100°C) = 76, content of monomer units derived from ethylene in (A4) = 69 mass%, content of monomer units derived from 5-ethylidene-2-norbornene in (A4) = 5 mass%, biomass degree of (A4) analyzed by ASTM D6866 = 71% (B4): Paraffin-based mineral oil manufactured by Idemitsu Kosan Co., Ltd. Product name: "Diana Process Oil PW380" (C1): Diisononyl phthalate manufactured by Tokyo Chemical Industry Co., Ltd. Product name: "Diisononyl phthalate (mixture of branched chain isomers)" (D1): Low density polyethylene, melting point 112℃, density 920kg / m 3 , content of monomer units derived from ethylene = more than 98% by mass (D1+E1): Sumika Color Co., Ltd. carbon black masterbatch product name "PEM-8080" (a mixture of 100 parts by mass of D1 (low-density polyethylene) and 100 parts by mass of E1 (carbon black)) (F1): Calcium carbonate manufactured by Nitto Funka Kogyo Co., Ltd. Product name "NS#100"

[0083] [Example 1] As raw materials, 100% by mass of (A1+B1) and 0.1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 1.

[0084] [Comparative Example 1] As raw materials, 100% by mass of (A1+B1) was melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt-kneading were measured. The measurement results and the blending amounts of each component are shown in Table 1.

[0085] [Example 2] As raw materials, 10% by mass of the composition obtained in Example 1 and 90% by mass of (A1+B1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 1.

[0086] [Comparative Example 2] As raw materials, 100% by mass of (A1+B1) and 1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 1.

[0087] [Table 1]

[0088] [Example 3] As raw materials, 100% by mass of (A2+B2) and 0.1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 2.

[0089] [Comparative Example 3] As raw materials, 100% by mass of (A2+B2) was melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 2.

[0090] [Example 4] As raw materials, 10% by mass of the composition obtained in Example 3 and 90% by mass of (A2+B2) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 2.

[0091] [Comparative Example 4] As raw materials, 100% by mass of (A2+B2) and 1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 2.

[0092] [Table 2]

[0093] [Example 5] As raw materials, 100% by mass of (A3+B3) and 0.1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 3.

[0094] [Example 6] As raw materials, 10% by mass of the composition obtained in Example 5 and 90% by mass of (A3+B3) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 3.

[0095] [Example 7] As raw materials, 10% by mass of the composition obtained in Example 6 and 90% by mass of (A3+B3) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 3.

[0096] [Comparative Example 5] As raw materials, 100% by mass of (A3+B3) and 1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of rotor temperature 70±10°C, rotation speed 60 rpm, and kneading time 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amount of each component are shown in Table 3.

[0097] [Table 3]

[0098] [Example 8] As raw materials, 50% by mass of (A2+B2), 0.1% by mass of (C1), 40% by mass of (D1+E1), and 10% by mass of (F1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 120±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 4.

[0099] [Example 9] As raw materials, 10% by mass of the composition obtained in Example 8, 45% by mass of (A2+B2), 36% by mass of (D1+E1), and 9% by mass of (F1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 120±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 4.

[0100] [Example 10] As raw materials, 10% by mass of the composition obtained in Example 9, 45% by mass of (A2+B2), 36% by mass of (D1+E1), and 9% by mass of (F1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 120±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 4.

[0101] [Comparative Example 6] As raw materials, 50% by mass of (A2+B2), 1% by mass of (C1), 40% by mass of (D1+E1), and 10% by mass of (F1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 120±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 4.

[0102] [Table 4]

[0103] [Comparative Example 7] As raw materials, 100% by mass of (A4) and 0.1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 5.

[0104] [Comparative Example 8] As raw materials, 10% by mass of the composition obtained in Comparative Example 7 and 90% by mass of (A4) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 5 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 5.

[0105] [Table 5]

[0106] [Comparative Example 9] As raw materials, 65% by mass of (A4) and 35% by mass of (B4) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 15 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 6.

[0107] [Example 11] As raw materials, 65% by mass of (A4), 35% by mass of (B4), and 0.1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 15 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 6.

[0108] [Example 12] As raw materials, 10% by mass of the composition obtained in Example 11, 58.5% by mass of (A4), and 31.5% by mass of (B4) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 15 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 6.

[0109] [Example 13] As raw materials, 10% by mass of the composition obtained in Example 12, 58.5% by mass of (A4), and 31.5% by mass of (B4) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 15 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 6.

[0110] [Comparative Example 10] As raw materials, 65% by mass of (A4), 35% by mass of (B4), and 1% by mass of (C1) were melt-kneaded in a 100cc Toyo Seiki Seisakusho Lab Plastomill under the conditions of a rotor temperature of 70±10°C, a rotation speed of 60 rpm, and a kneading time of 15 minutes. The average shear viscosity and average die swell ratio of the composition obtained by melt kneading were measured. The measurement results and the blending amounts of each component are shown in Table 6.

[0111] [Table 6]

[0112] As can be seen from the results in Tables 1 to 6, the thermoplastic resin compositions of the examples which satisfy all of the constituent requirements of the present invention have a relatively small die swelling ratio during extrusion molding.

Claims

1. (A) an ethylene-α-olefin-non-conjugated diene copolymer, (B) a mineral oil, and (C) a phthalate ester; (C) the content of phthalate ester is 5 ppm or more and 10,000 ppm or less based on 100 parts by mass of the (A) ethylene-α-olefin-non-conjugated diene copolymer, (C) A thermoplastic resin composition, wherein the phthalate ester is diisononyl phthalate.

2. The thermoplastic resin composition according to claim 1, wherein the content of the mineral oil (B) is 30 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A).

3. The thermoplastic resin composition according to claim 1, further comprising at least one member selected from the group consisting of calcium carbonate and carbon black.

4. The thermoplastic resin composition according to claim 1, further comprising (D) an olefin-based polymer (excluding (A) the ethylene-α-olefin-non-conjugated diene copolymer).

5. 5. The thermoplastic resin composition according to claim 4, wherein the olefin polymer (D) is at least one selected from the group consisting of ethylene polymers and propylene polymers.

6. The thermoplastic resin composition according to claim 1, wherein the content of the phthalate ester (C) is 50 ppm or more and 5,000 ppm or less based on 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A).

7. The thermoplastic resin composition according to claim 1, wherein the content of the mineral oil (B) is 50 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the ethylene-α-olefin-non-conjugated diene copolymer (A).

8. The thermoplastic resin composition according to claim 1, wherein the content of monomer units derived from non-conjugated diene in the ethylene-α-olefin-non-conjugated diene copolymer (A) is 4% by mass or more and 15% by mass or less.

9. (A) Mooney viscosity (ML 1+4 The thermoplastic resin composition according to claim 1, wherein the melting point (100°C) is 40 or more.

10. Temperature: 220°C, shear rate: 1216 sec -1 The thermoplastic resin composition according to claim 1, having a shear viscosity of 50 Pa·sec or more and 600 Pa·sec or less.

11. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Ethylene propylene diene monomer heat-conducting rubber

    CN103044785A

  • Anticorrosion flame resistant cable and preparation method thereof

    CN109651721A

  • Room temperature shrinkable tube for cable connection part and rubber composition used for the same

    JP2002260469A

  • Resin composition for automotive door grommet and automotive door grommet

    JP2002265715A

  • Dynamically crosslinked thermoplastic elastomer composition and its manufacturing method as well as molded body

    JP2020143253A